A Nonconserved Surface of the TFIIB Zinc Ribbon Domain Plays a Direct Role in RNA Polymerase II Recruitment - Tubon, Thomas C. (American Society for Microbiology, 2004)
The general transcription factor TFIIB is a highly conserved and essential component of the eukaryotic RNA polymerase II (pol II) transcription initiation machinery. It consists of a single polypeptide with two conserved structural domains: an amino-terminal zinc ribbon structure (TFIIB(ZR)) and a carboxy-terminal core (TFIIB(CORE)). We have analyzed the role of the amino-terminal region of human TFIIB in transcription in vivo and in vitro. We identified a small nonconserved surface of the TFIIB(ZR) that is required for pol II transcription in vivo and for different types of basal pol II transcription in vitro. Consistent with a general role in transcription, this TFIIB(ZR) surface is directly involved in the recruitment of pol II to a TATA box-containing promoter. Curiously, although the amino-terminal human TFIIB(ZR) domain can recruit both human pol II and yeast (Saccharomyces cerevisiae) pol II, the yeast TFIIB amino-terminal region recruits yeast pol II but not human pol II. Thus, a critical process in transcription from many different promoters—pol II recruitment—has changed in sequence specificity during eukaryotic evolution.